Optimization of Rotation Speed, Disc Diameter, and Lighting Time in Batik Waste Treatment Using Rotary Algae Biofilm Reactor (RABR) with Ulva sp. - Raharjo, Sonya Hakim; Palupi, Bekti; Syaifullah, Rangga Yudha; Yohanes; Sekaringgalih, Ratri; Hidayati, Nurul (Eksergi, 2025)
Batik is one of the cultural heritages in Indonesia that must be maintained and preserved. The batik industry process itself produces liquid waste that comes from the coloring processing, washing, wax removing, also rinsing. Batik waste, if not treated properly, can harm the environment. Various studies have shown that effluent treatment using the Rotary Algae Biofilm Reactor (RABR) method is promising. This research focuses on improving the RABR design and optimal conditions for treating batik wastewater, as well as utilizing the synergy between batik production and Ulva sp. The variables used in this research are the rotation speed of 20, 30, and 40 rpm, the lightning time for 0, 6, and 12 hours, and the disk diameter size of 9, 11, and 13 cm. The parameters that analyzed are BOD, COD, and pH levels. Waste treatment optimization in this research uses the RSM with a combination of Design Expert 13 software. Based on the results, the most optimal batik wastewater treatment variable is when the disk diameter is 10.306 mm, the rotation speed is 20 rpm, and the lightning time is 7.805 hours, yielding response values of 55.673 mg/L for BOD, 25.538 mg/L for COD, and 10.406 for pH.